Study on Skid Resistance of Asphalt Pavements Under Macroscopic and Microscopic Texture Features: A Review of the State of the Art - Wei Chen; Zhengchao Zhang; Jincheng Wei; Xiaomeng Zhang; Wenjuan Wu; Yuxuan Sun; Guangyong Wang (Applied Sciences)
Pavement skid resistance is one of the most important factors affecting road safety, and pavement texture morphology significantly influences this property. Therefore, it is crucial to investigate the relationship between pavement texture and skid resistance. This article provides an overview of recent research advancements in key areas, including the anti-skid mechanisms of asphalt pavements, factors affecting pavement anti-skid performance, methods for characterising and evaluating pavement anti-skid performance, and the relationship between the macroscopic and microscopic texture of pavements and their anti-skid performance. Based on a comparative analysis of the intrinsic mechanical interactions between asphalt pavements and rubber tyres, it was determined that the surface texture characteristics of the asphalt pavement are the most critical factor influencing its anti-skid performance. These include both macroscopic and microscopic texture parameters, which, together with the service environment, collectively influence the pavement’s anti-skid performance. The existing texture characteristics, based on the anti-skid performance of asphalt pavements, as detected by various methods and evaluated using established models, are summarised here. Finally, this article discusses the relationship between texture characteristic parameters and asphalt pavement anti-skid performance from both macro- and microtexture perspectives. This synthesis serves as a valuable reference and basis for further research and development in enhancing asphalt pavement skid resistance.